Digital Literacy in Pre-Service English Teachers’ Professional Development: Perspectives and Challenges - Hariro, Khoiriyatul Hariro (Perkumpulan Dosen dan Pengajar Bahasa Inggris Se-Indonesia (ELITE Association Indonesia), 2024)
Teachers require technology and digital literacy to enhance their teaching and learning activities. Digital literacy stands as a crucial skill in the preparation of pre-service teachers for their roles in the pedagogical realm. Among the skills emphasized in their professional development, digital literacy assumes significance. Teachers, including pre-service English teachers, should promote digital literacy in teaching and learning activities by providing the use of technology and digital tools to create more interesting, meaningful, and interactive materials, media, and activities. This study aims to investigate the pre-service English teachers’ perspectives on their levels of digital literacy and to examine the software tools and applications commonly used by them. It also aims to explore the challenges in promoting digital literacy in pre-service English teachers’ professional development. In this study, a mixed-methods research design was employed, integrating both qualitative and quantitative approaches. Data collection involved administering a closed-ended questionnaire to 67 participants and conducting interviews with 10 participants from the same population. Quantitative data were analyzed using descriptive statistical analysis with SPSS 20, while qualitative data were interpreted through descriptive explanations. The results showed that mostly pre-service English teachers have high level and medium level of digital literacy. Microsoft Office Word was the software or application which was the most commonly used by them. The results also showed that there were five challenges faced by pre-service English teachers in promoting digital literacy in their professional development which were: 1) lack of technology facilities and accessibility; 2) lack access of the internet connection; 3) choosing appropriate digital tools for teaching materials and media; 4) not providing sufficient budget to invest on educational technology; and 5) lack of competence to use English educational technology.